Bulgaria : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bulgaria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The large capital inflows that generated a domestic demand boom in Bulgaria led to strong employment growth. But a sharp reduction in capital inflows led to a contraction of domestic demand, while the recession in Bulgaria's trading partners caused a drop in exports. Public policies will also need to attune to the domestic demand-driven revenue boom and adjust spending growth to the new environment. Capital inflows are likely to remain low, and domestic demand is expected to decline further, requiring substantial adjustments by both the private and public sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet